2019
DOI: 10.2320/matertrans.mf201937
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Vacancies during Severe Plastic Deformation

Abstract: A high density of lattice defects is introduced to materials by severe plastic deformation (SPD). Numerous experimental techniques, in particular electron microscopy, X-ray, electron and neutron diffraction, etc. are employed to characterize the evolution of microstructure and defects with strain introduced to the material by SPD. These techniques concentrate mainly on the investigation of planar (grain boundaries) and line defects (dislocations). On the other hand, point defects, namely vacancies and their ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 70 publications
2
18
0
1
Order By: Relevance
“…It is then concluded that HPT processing can induce oxygen vacancies in SiO 2 in good agreement with the earlier reports on the formation of vacancies in the HPT‐processed TiO 2 , 11 ZnO, 12 TiO 2 ‐ZnO, 13 Al 2 O 3 , 14,15 BaTiO 3 16 and ZrO 2 , 17 LiTaO 3 18 and GaZnON 22 . The formation of vacancies by HPT processing is usually attributed to the effect of strain on continuous formation of vacancies and to the effect of pressure on suppressing the migration and annihilation of vacancies 3,70–72 . The formation of oxygen vacancies by HPT suggests a possible pressure‐temperature‐strain‐based mechanism for the formation of vacancies in SiO 2 ‐based minerals and sands 73–75 …”
Section: Resultssupporting
confidence: 88%
“…It is then concluded that HPT processing can induce oxygen vacancies in SiO 2 in good agreement with the earlier reports on the formation of vacancies in the HPT‐processed TiO 2 , 11 ZnO, 12 TiO 2 ‐ZnO, 13 Al 2 O 3 , 14,15 BaTiO 3 16 and ZrO 2 , 17 LiTaO 3 18 and GaZnON 22 . The formation of vacancies by HPT processing is usually attributed to the effect of strain on continuous formation of vacancies and to the effect of pressure on suppressing the migration and annihilation of vacancies 3,70–72 . The formation of oxygen vacancies by HPT suggests a possible pressure‐temperature‐strain‐based mechanism for the formation of vacancies in SiO 2 ‐based minerals and sands 73–75 …”
Section: Resultssupporting
confidence: 88%
“…It is then concluded that HPT processing can induce oxygen vacancies in CsTaO3 and LiTaO3 in good agreement with the earlier reports on the formation of oxygen vacancies in the HPT-processed BaTiO3 [37], TiO2 [30], ZnO [31], Al2O3 [33,40] and TiO2-ZnO [32]. The formation of vacancies by HPT processing is due to the strain effect on continuous generation of vacancies and the pressure effect on suppressing the migration and annihilation of vacancies [46][47][48].…”
Section: Resultssupporting
confidence: 87%
“…Early modeling by Mecking et al [12] suggested that vacancy supersaturation by deformation in the power-law regime was unlikely, but suggested that supersaturation may occur within PLB. More recently, important modeling and experiments by others [13][14][15] also suggested that supersaturation may occur with significant plasticity within PLB. Wu and Sherby [16] however, subsequently suggested that internal stress, as did Nix and Ilschner, albeit from different sources, explains PLB behavior and appeared to abandon vacancy superstation effects.…”
Section: Discussionmentioning
confidence: 98%
“…If we assume just volume diffusion at ambient temperature for silver, which appears to achieve steady-state after strains greater than 3.0 at ambient temperature, the predicted vacancy concentration (based on the usual equations [27]) is roughly 10 −17 . With substantial plasticity (e.g., >0.3) the latest experimental and theoretical estimates [12][13][14][15]28] of the vacancy concentration at ambient temperature after large strain deformation in metals is of the order of 10 −3 to 10 −5 (roughly a factor of 10 13 higher than the equilibrium concentration). This suggests that the low-temperature diffusion coefficient may be relatively high giving rise to higher than expected creep rates leading to PLB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation